Teacher’s Efforts to Improve Students’ Activity and Learning Outcomes through Classroom Meeting at SMK Budi Luhur Tebo Jambi - Yulia Wiji Astika (Journal of Research in Business, Economics, and Education, 2022)
Learning is a conscious and planned effort to create learning atmosphere. In order student become good student, the learning process was carried out interactively. When the learning was carried out, the students only received the material provided by the teacher. The aim of this research was to know the teacher's efforts to improve students’ activity and learning outcomes through Classroom Meeting at SMK Budi Luhur. The method used Classrom Action Research conducted in class X TKJ with 30 students. The types data used qualitative and quantitative data. This research was conducted in three cycles consisted of cycle I, II and III which has stages were planning, actions, observing, analyzing and reflecting. The result of this study was using Classroom Meeting could increase students’ activity. It was indicated by the students who pay attention when the teacher presents the subject from 50% in first cycle, 73% in second cycle, 83% in cycle III. Then, when the teacher presents problems increased from 30% in first cycle, 77% in second cycle, 87% in third cycle. Students who dared to pose problems from 3% in first cycle, 17% in second cycle, then 37% in third cycle. Students who dared to express their opinions from 17% in first cycle, 53% in second cycle, then 73% in third cycle. Students who dare to give comments from 17% in first cycle, 50% in second cycle, then 87% in third cycle. Students who participated in making conclusions from 17% in first cycle, 50% in second cycle, then 80% in third cycle. Students who actively answered questions from 17% in first cycle, 60% in second cycle, then increased 87% in third cycle. The use of Classroom Meeting could improve student learning outcomes. It was indicated by 5.27 in cycle 1, and 6.54 in cycle II and 7.67 in cycle III.